Lipid Nanoparticles: Application in Cancer Therapy - Salunkhe, S. M.; Gambhire, V. M.; Gujar, K. N.; Gambhire, M. S. (Asian Journal of Pharmaceutical Research and Development, 2014)
Several obstacles frequently encountered with anticancer drugs, such as normal tissue toxicity, stability, poor specificity and a high incidence of drug resistant tumor cells, are overcome by delivering them using Lipid Nanoparticles (LNs). LNs include Solid Lipid Nanoparticles (SLNs) and Nanostructured Lipid Carriers (NLCs), which have been developed by most of researchers for cancer therapy. The SLNs and NLCs because of submicron-sized particulate matter may preferentially extravasate into the tumor and be retained there to achieve passive tumor targeting. The advances in surface-engineering technology modified the surface physico-chemical properties of LNs to target them to the tissue of interest. This maximizes the amount of drug that can reach the targeted tumor sites and minimizes systemic drug toxicity. The emergence of the newer forms of LNs such as polymer– lipid hybrid nanoparticle and long-circulating SLN may further expand the role of this versatile drug carrier in cancer therapy. In the present review, an attempt has been made to highlight the importance of solid lipid nanoparticles and nanostructured lipid carriers in anticancer drug delivery. The discussion includes obstacles in cancer therapy, rationale of using lipid nanoparticles in cancer therapy, significant anticancer activity of LNs -encapsulated cytotoxic drugs, future directions for SLN and NLC- based delivery systems in cancer therapy. In the near future, LNs will be further improved to deliver anticancer compounds in a more efficient, specific and safer manner.